2021
DOI: 10.3390/life11030230
|View full text |Cite
|
Sign up to set email alerts
|

Arthritogenic Alphavirus Capsid Protein

Abstract: In the past two decades Old World and arthritogenic alphavirus have been responsible for epidemics of polyarthritis, causing high morbidity and becoming a major public health concern. The multifunctional arthritogenic alphavirus capsid protein is crucial for viral infection. Capsid protein has roles in genome encapsulation, budding and virion assembly. Its role in multiple infection processes makes capsid protein an attractive target to exploit in combating alphaviral infection. In this review, we summarize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…The diversity of the receptor-binding domain might determine the host tropisms of alphaviruses. The CP provides a physical protection shell for the viral genome RNA and may also be involved in viral genome replication [25].…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of the receptor-binding domain might determine the host tropisms of alphaviruses. The CP provides a physical protection shell for the viral genome RNA and may also be involved in viral genome replication [25].…”
Section: Introductionmentioning
confidence: 99%
“…The multifunctional arthritogenic alphavirus capsid protein is crucial for viral infection and has roles in genome encapsulation, budding, and virion assembly. The arthritogenic alphaviral capsid protein can play an important role in vaccine design, can be regarded as a therapeutic target, and can play an important role in the development of diagnosis ( Rao and Taylor, 2021 ). CHIKV can be genetically divided into three lineages: West African; East, Central, and South African; Indian Ocean; and Asian.…”
Section: Resultsmentioning
confidence: 99%
“…All the non-structural proteins (nsP1-nsP4) are normally required for RNA synthesis [ 49 ], but the nsP2 protein is established as a virulence factor and inhibitor of the IFN-induced JAK/STAT pathway [ 48 ]. In addition, the essential interactions between the capsid protein and the E1 or E2 protein has also been underlined [ 50 ]. We showed that all the studied compounds efficiently downregulated E1 and E2 gene expression during ONNV infection, in spite of a distinct upregulation of capsid and nsP2 gene expression by MAT.…”
Section: Discussionmentioning
confidence: 99%